Credit growth in Central and Eastern Europe: Convergence or boom? - Gergely Kiss; Márton Nagy; Balázs Vonnák (Magyar Nemzeti Bank, 2006)
Credit to the private sector has been growing very rapidly in a number of Central and Eastern European countries in recent years. The main question is whether this dynamics is an equilibrium convergence process or may rather pose stability risks. Using panel econometric techniques, this paper attempts to identify the equilibrium credit/GDP levels of the new EU countries, disentangling the observed growth into an equilibrium trend and an excess (boom) component. In the paper the pooled mean group estimator was used for its flexibility and efficiency. Using instrumental variable technique we tested whether long run endogeneity affects the consistency. The estimations show that large part of the credit growth in new member states can be explained by the catching-up process, and, in general, credit/GDP ratios are below the levels consistent with macroeconomic fundamentals. However, in Latvia and Estonia credit growth is found to be significantly faster than what would be justified along the equilibrium path.
Keywords: E44; O16; 330; financial deepening; credit growth; transition economies; panel econometrics; endogeneity bias; Kredit; Gleichgewicht; Entwicklungskonvergenz; Schätzung; EU-Staaten (Osteuropa)